A Domain Ontology for Eliciting Usability Features - Wen Too, Chian; Hassan, Sa’adah; Azim Abdul Ghani, Abdul; Din, Jamilah (International Journal of Engineering and Technology, 2018)
One of the crucial factors that can influence user preferences of software is usability.Â It assesses the extent of which software able to facilitate user and use the software easily and effectively.Â Typically, usability requirements are specified at the design stage of software development due to its characteristic that is subjective in nature and hard to be elicited at the early stage. As a result, the lack identification and improper treatment of usability features always caused the failure of a software product. Consequently, it increased the cost and effort of rework. Essentially, it suggested that usability need to be specified at the requirements engineering stage to complement the software functional requirements.Â This paper presents a preliminary study on current efforts to support the activities in identifying usability attributes in the software functional requirements. The potential of adopting pattern and ontology for identifying usability features are also presented. The development of domain ontology is proposed to fill the gap of the current efforts where there is lack of usability driven semantic knowledge model to support the usability elicitation tasks. The designed domain ontology is expected to overcome the problems resulted from software developer that lack of sufficient knowledge or expertise in eliciting usability features at requirements engineering level. The main contribution is to provide a guideline to aid the requirements engineer to elicit and specify usability requirements start from the early stage of development phases. Â Â Â